Examining the potential preventability of adverse fetal/neonatal outcomes associated with severe maternal morbidity. (7th July 2021) - Lawton, Beverley; MacDonald, Evelyn Jane; Filoche, Sara; Stanley, James; Meeks, Maggie; Stone, Peter; Storey, Francesca; Geller, Stacie E.
Abstract : Background: Severe maternal morbidity (SMM) occurs in 1–2% of pregnancies. Despite the knowledge that a SMM event can contribute to poor fetal/neonatal outcomes, little is known about the preventability of these adverse outcomes. Aims: To examine adverse fetal/neonatal outcomes associated with SMM to determine if these outcomes were potentially preventable. Materials and Methods: A New Zealand national retrospective cohort study examining cases of SMM with an adverse fetal/neonatal outcome. Maternity and initial neonatal care were explored by multidisciplinary panels utilising a preventability tool to assess whether the fetal/neonatal harm was potentially preventable. Adverse fetal/neonatal outcomes were defined as fetal or early neonatal death, Apgar score <7 at five minutes, admission to neonatal intensive care unit or special care baby unit and neonatal encephalopathy. Results: Of 85 cases reviewed, adverse fetal/neonatal outcome was deemed potentially preventable in 55.3% of cases ( n = 47/85). Preventability was related to maternal antenatal/peripartum care ( in utero ) in 39% ( n = 33/85), to initial neonatal care ( ex utero ) in 36% ( n = 29/80), and to both maternal and neonatal care in 20% (16/80) of cases. Main contributors to potential preventability were factors related to healthcare providers, particularly lack of recognition of high risk, delayed or failure to diagnose, and delayed or inappropriate treatment. Conclusions: Multidisciplinary panels found that over half of adverse fetal/neonatal harm associated with SMM was potentially preventable. The novel approach of examining both maternal and neonatal care identifies opportunities to improve fetal/neonatal outcomes associated with SMM at multiple points on the perinatal continuum of care.